Influence of different proportions of external irrigation during the Er, Cr: YSGG laser irradiation on wear and roughness of root surface - Pimente, Guilherme José [UNESP]; Oliveira, Lopes de; Pinotti, Felipe Eduardo [UNESP]; Carvalho, Heglécia da Luz [UNESP]; Scardueli, Cássio Rocha [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP] (Maad Rayan Publishing Company, 2016)
Introduction: The aim of this study was to evaluate the influence of different levels of external irrigation during irradiation with an erbium, chromium: yttrium-scandium-gallium-garnet (Er, Cr:YSGG) laser on the roughness and wear of dental tissue during scaling procedures. Methods: Twenty-Five uniradicular bovine teeth had the proximal surfaces planed and divided into 3 regions: upper, middle and lower. The upper region was treated with hand instruments, the middle region was not treated and served as a control, and the lower region was treated by the Er, Cr:YSGG laser. The teeth were randomly divided into five groups according to the different proportions of external irrigation used during the laser irradiation: G1: 10%; G2: 20%; G3: 30%; G4: 40% and G5: 50%. The samples were analyzed for roughness and wear on the root surface irradiated with the laser. Results: There were no differences in the surface roughness and wear parameters between the groups irradiated with the laser, but the laser irradiation produced a rougher surface of the dentin than treatment with hand scaling. Conclusion: Changes in the external irrigation level did not influence the wear and roughness of root surfaces treated with an Er, Cr:YSGG laser.
Keywords: Dental scaling; Laser; Roughness; Tooth wear